Introversion and High Spatial Ability Is Associated With Origami Proficiency - Hanada, Mitsuhiko (Frontiers in Psychology, 2022)
This study examined the relationship between origami performance, personality traits, and spatial ability. The researchers asked 43 Japanese university students (19 women and 24 men) to fold three models of origami (paper folding). Their performance was assessed by the number of successes in correctly folding the paper to make the models. They also answered the personality inventory NEO-FFI and completed the block-design test of the Wechsler Adult Intelligence Scale IV, which measures the spatial ability of people. The results showed that although origami performance demonstrated no significant relation with neuroticism, openness to experience, agreeableness, or conscientiousness, it improved as introversion tendency and spatial ability increased. There were no differences based on sex in origami performance. The findings suggest that performing origami requires spatial ability, which supports the view that origami is a potential educational material for training and enhancing spatial ability, and that introversion is advantageous to origami performance.